2017
DOI: 10.1186/s13059-017-1165-7
|View full text |Cite
|
Sign up to set email alerts
|

BaalChIP: Bayesian analysis of allele-specific transcription factor binding in cancer genomes

Abstract: Allele-specific measurements of transcription factor binding from ChIP-seq data are key to dissecting the allelic effects of non-coding variants and their contribution to phenotypic diversity. However, most methods of detecting an allelic imbalance assume diploid genomes. This assumption severely limits their applicability to cancer samples with frequent DNA copy-number changes. Here we present a Bayesian statistical approach called BaalChIP to correct for the effect of background allele frequency on the obser… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…This is conveniently provided by ASB data. We collected ASB variants from five studies [14][15][16][17][18] , with each study providing heterozygous variants, the sample or cell line from which it was obtained, and reference and alternate allele read counts and the TF affected ( Figure 1a). Since read counts were collected from different sources and processed with their respective analysis pipelines, we also ensured results from different studies were consistent with one another where possible.…”
Section: A Compendium Of Allele-specific Binding Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is conveniently provided by ASB data. We collected ASB variants from five studies [14][15][16][17][18] , with each study providing heterozygous variants, the sample or cell line from which it was obtained, and reference and alternate allele read counts and the TF affected ( Figure 1a). Since read counts were collected from different sources and processed with their respective analysis pipelines, we also ensured results from different studies were consistent with one another where possible.…”
Section: A Compendium Of Allele-specific Binding Eventsmentioning
confidence: 99%
“…ASB data were collected from five studies [14][15][16][17][18] . In each study, ChIP-seq reads are mapped to both alleles of heterozygous variants in individuals or cell lines.…”
Section: Collection Of Allele-specific Binding Datamentioning
confidence: 99%
“…We assessed the degree of allele bias, measured as the fraction of ChIP-seq reads containing the reference sequence (hg19), for each DAP at all heterozygous single-nucleotide variants (SNVs) that overlapped with an adult DAP binding site (DeSantiago et al 2017). Correlation analyses of the degree of allele bias at each SNV between all possible pairs of DAPs revealed that factors possessed highly correlated allele biases, indicating that groups of DAPs bound near one another show preference for the same allele ( Fig.…”
Section: Daps Display Extensive Colocalizationmentioning
confidence: 99%
“…Allele bias in DAP occupancy was assessed with ChIP-seq data using the R package "BaalChIP" (DeSantiago et al 2017). Allele-specific expression was calculated for each expressed heterozygous SNP using the GATK "ASEReadCounter" function according to previously described best practices (Castel et al 2015).…”
Section: Allele-specific Binding and Expression Analysismentioning
confidence: 99%
“…Our method is developed based on the established strategy for conducting allele-specific analysis on many types of sequencing data, which specifically focus on the sequencing reads on heterozygous loci. This includes allele-specific gene expression ( Zhang et al, 2014 ; Castel et al, 2015 ), allele-specific alternative splicing analysis ( Nembaware et al, 2008 ; Li et al, 2012 ), allele-specific binding of ChIP-seq ( de Santiago et al, 2017 ) and CLIP-seq data analysis ( Yang et al, 2019 ), allele-specific chromatin interaction ( Cavalli et al, 2019 ), and allele-specific chromatin accessibility ( Harvey et al, 2014 ; Zhang et al, 2019 ). To our knowledge, our method is the first to analyze allele-specific footprint.…”
Section: Discussionmentioning
confidence: 99%